Akuisisi sebagai Bentuk Integrasi Vertikal dalam Industri Penyiaran Televisi dan Implikasinya terhadap Persaingan Usaha - Hidayatulloh, Ilham Gusti Nur; Wiwoho, Jamal (Indonesian Journal of Social Sciences and Humanities, 2026)
The development of the television broadcasting industry in Indonesia has demonstrated an increasing trend of consolidation through acquisitions, potentially resulting in vertical integration between content producers and broadcasting channel operators. This article aims to analyze acquisitions as a form of vertical integration in the television broadcasting industry and their implications for business competition under Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. This research employs a normative legal method using statutory and conceptual approaches, supported by an analysis of the structural characteristics of the broadcasting industry. The findings indicate that although Article 14 of Law No. 5 of 1999 textually regulates vertical agreements, acquisitions that create control across different market levels may be qualified as vertical integration under a systematic and effects-based interpretation. Vertical integration through acquisition is not strictly prohibited but is assessed using a rule of reason approach by balancing efficiency gains against the risk of vertical foreclosure, particularly in industries characterized by limited distribution channels and high entry barriers. Therefore, the legality of such acquisitions depends on whether they restrict market access and distort competitive market structures.